Acaricidal and Repellence of R. appendiculatus, and GC-MS Chemical Content of Essential Oils from Three South African Ethno-Veterinary Plants - Mkolo, N.M.; Gumede, B.T.; Magano, S.R.; Olaokun, O.O. (Asian Journal of Chemistry, 2021)
The advancement of the livestock farming in sub-Saharan Africa is restricted by tick infestation. With conventional pesticides posing a threat to human and the environment, natural products are alternative anti-tick source. This study characterized the essential oils from Tithonia diversifolia, Lavandula angustifolia and Cymbopogon citratus leaves by GC-MS and, for acaricidal and repellence of R. appendiculatus. GC-MS analysis detected various chemical compounds, some of the isolated compounds have anti-tick properties. The repellence of T. diversifolia essential oil at 5% v/v was the weakest against adult ticks. All essential oils at 15% v/v paralysed nymph after 20 mins, with C. citratus after 24 h causing high mortality of nymph and adult ticks. Exposure to L. angustifolia did not achieve 50% mortality after 24 h. All essential oils caused complete inhibition of moulting of engorged larvae. The study demonstrated that the essential oils of the ethno-veterinary plants may be a source of anti-ticks agents.